Does On-Line Shop Influence The Volume of Sales? - Nendah Dewi Yuningsih; Rieke Retnosary; Dini Yani (Yayasan Riset dan Pengembangan Intelektual, 2024)
Dhinda hijab store, one of the micro, small, and medium enterprises in Karawang City, implements an inclusive marketing strategy. This shop actively participates in sales through the e-commerce platform Shopee and also opened a physical shop in Karawang downtown. Dhinda hijab store develops a marketing network by having resellers help distribute its products. To increase sales volume on the Shopee e-commerce platform, Dhinda hijab store is running various promotional features. Dhinda uses product advertising, holds live streaming, and arranges attractive store decorations to attract consumer attention.